Effects of Dual‐Task and Single‐Task Interventions on Physical and Cognitive Function in Older Adults: A Scoping Review. - Thazhakkattu Vasu, Deepak; Pan Jia Yee, Tammy; Chou, Li-Wei; Lai Yen, Fong; Karalı, Fenise Selin (Journal of Aging Research, 2026)
Background: Dual‐task and single‐task interventions are strategies to enhance physical and cognitive function in older adults, but their effectiveness in comparison is not well understood. Understanding their effects on cognitive benefits, balance, and overall physical performance is important for developing effective interventions to support aging populations. Objective: This scoping review aims to identify and synthesize current evidence on dual‐task and single‐task interventions for older adults, categorizing intervention types, study populations, and measured outcomes. Methods: PubMed, MEDLINE, Scopus, and Web of Science databases were searched. A comprehensive literature search identified studies involving dual‐task and single‐task interventions from 2014 to July 2024 involving adults aged 60 and older. The methodological quality of the included studies was assessed using the Mixed‐Methods Appraisal Tool (MMAT). Studies were categorized based on task type: motor–cognitive dual‐task, motor–motor dual‐task, single‐motor task, or single cognitive task. Extracted data included intervention characteristics, outcome measures, and key findings. Results: A total of 31 studies met the inclusion criteria with participants being community‐dwelling older adults aged 60 and above. Intervention durations ranged from 6 weeks to 12 months, with most studies implementing sessions 2‐3 times per week. Outcome measures commonly included assessments of balance, cognitive function, and gait performance. Dual‐task interventions demonstrated greater improvements in gait, dynamic balance, and cognitive function compared to single‐task interventions with motor‐cognitive dual‐task training being particularly effective in enhancing balance and mobility in older adults. Conclusion: This review provides a comprehensive comparison of dual‐task and single‐task interventions, highlighting the superior efficacy of dual‐task training in improving both cognitive and physical outcomes. While single‐task interventions offer benefits, they lack the comprehensive improvements observed in dual‐task training. Future research should explore long‐term outcomes, refine intervention protocols, and assess the applicability of combined approaches to maximize benefits for aging populations. And, studies must prioritize reporting effect sizes and minimum clinically important differences (MCID) to ensure findings are clinically relevant.